Teachers’ Strategies in Developing Students’ Self-Confidence - Rijnan (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2026)
Self-confidence is an essential psychological factor that influences students’ academic performance, social interaction, and emotional development. Teachers play a crucial role in shaping students’ confidence through instructional strategies, classroom management, and interpersonal communication. This study aims to explore teachers’ strategies in developing students’ self-confidence and analyze their impact on learning engagement. The research employed a qualitative descriptive approach involving classroom observations, interviews with teachers, and documentation analysis. The findings indicate that teachers apply various strategies such as positive reinforcement, student-centered learning, cooperative learning, public speaking activities, and emotional support. These strategies significantly contribute to increasing students’ participation, motivation, and self-belief. The study concludes that consistent and supportive teaching strategies are essential for fostering students’ self-confidence and creating a positive learning environment.